2007
DOI: 10.1143/jjap.46.1286
|View full text |Cite
|
Sign up to set email alerts
|

Defect Reduction in Polycrystalline Silicon Thin Films by Heat Treatment with High-Pressure H2O Vapor

Abstract: The dynamics of vibrational energy relaxation by collisions in molecular beams and free jet expansions are examined. Within the stochastic approach afforded by the use of the master equation, the incomplete relaxation process may be modelled by assuming a time-dependent transition rate matrix. In particular, we prove that for non-degenerate levels and weak interactions the state distribution is Boltzmannian if the transition rate matrix is of the Landau-Teller type. The ramifications of this result on the anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 10 publications
1
14
0
Order By: Relevance
“…A long time is necessary for reducing the defect density. Our recent study revealed that the oxygen concentration increased after high-pressure H 2 O vapor heat treatment, and that the hydrogen concentration decreased [29]. These results indicate a possibility that dangling bonds are well oxidized and oxygen atoms terminate dangling bonds at grain boundaries.…”
Section: Structural and Electrical Propertiesmentioning
confidence: 86%
“…A long time is necessary for reducing the defect density. Our recent study revealed that the oxygen concentration increased after high-pressure H 2 O vapor heat treatment, and that the hydrogen concentration decreased [29]. These results indicate a possibility that dangling bonds are well oxidized and oxygen atoms terminate dangling bonds at grain boundaries.…”
Section: Structural and Electrical Propertiesmentioning
confidence: 86%
“…This energy is required for both production of passivation particles from H 2 O molecules and for their effective diffusion inside silicon. According to the literature , these particles can be, e.g. −OH, −H, and −OOH.…”
Section: Discussionmentioning
confidence: 99%
“…The best silicon electrical quality characterised by solar cell's V OC was 497 mV achieved at the temperature of 600 8C, the hydrogen pressure of 500 Pa after 15 min. [14,[20][21][22][23][24][25][26], these particles can be, e.g. ÀOH, ÀH, and ÀOOH.…”
Section: Plasma Hydrogenationmentioning
confidence: 99%
“…High-pressure H 2 O vapor heat treatment was developed to reduce the density of defect states in SiO 2 , a-Si, and poly-Si films and their interfaces [5][6][7][8][9]. H 2 O vapor molecules incorporate into those films and effectively terminate electrical active silicon dangling bonds.…”
Section: High-pressure H 2 O Vapor Heat Treatment To Silicon Filmsmentioning
confidence: 99%